Photoacoustic imaging of oil-treated tissues for the potential support of halal product identification - Putut Giri Tulus Widodo; Mitrayana Mitrayana (Journal of Physics: Theories and Applications, 2025)
Photoacoustic Imaging (PAI) has successfully demonstrated its capability as a non-destructive method for distinguishing biological tissues based on oil absorption characteristics. Chicken meat samples were soaked in coconut oil, sesame oil, and lard for 10 minutes, 60 minutes, and 24 hours. The PAI system employed a 532 nm green laser, condenser microphone, and a two-dimensional scanning stage to capture spatial images. Grayscale and pseudocolor images were analyzed to extract numerical features including mean intensity, standard deviation, and entropy. Results showed that tissues treated with lard consistently exhibited higher values of numerical feature, particularly after 24 hours, compared to samples with vegetable oils. These variations are linked to stronger optical absorption and increased structural complexity caused by oil infiltration. The study demonstrates that PAI can effectively detect oil-specific changes in tissue, suggesting its potential role in supporting halal product verification.